miR-629-3p Level Significantly Predicts Prognosis in Glioblastoma Patients Treated with Temozolomide Chemotherapy - Hui-Yuan, Chen; Wen-Bin, Li; Chuan-Bao, Zhang; Wei, Zhang; Hu-Yong, Zheng (Current Signal Transduction Therapy, 2014)
Background: Glioblastoma is the most aggressive and common primary tumor of the central nervous system. Resistance to temozolomide, the first-line chemotherapy for glioblastoma, always leads to treatment failure. Further understanding of the molecular mechanisms of temozolomide resistance in glioblastoma is desperately needed. The purpose of this study was to identify miRNAs correlated with temozolomide treatment in glioblastoma paitents. Methods: miRNA expression microarray data of 82 glioblastoma samples were obtained from the Chinese Glioma Genome Atlas database (http://www.cgga.org.cn). In order to identify miRNAs correlated with temozolomide reponse, the significance of the association between each miRNA expression and overall survival of temozolomide treated glioblastoma patients was analyzed by univariate Cox proportional hazard regression analysis. Gene expression profile associated with miR-629-3p was determined using whole genome mRNA expression microarray data. Subsequently, biological progresses related to the miR-629-3p associated gene expression profile were identified by gene ontology analysis Results: The miR629-3p level was significantly correlated with overall survival in patients who underwent temozolomide chemotherapy, while a higher miR629-3p level failed to improve overall survival in patients who had not received temozolomide treatment. Gene ontology analysis showed that miR-629-3p associated genes were involved in the biological processes including translation, translational elongation, and ribonucleoprotein complex biogenesis. Conclusion: High-level miR629-3p expression was associated with prolonged overall survival in patients who underwent temozolomide chemotherapy, indicating that miR-629-3p may be a predictive biomarker for temozolomide response, a guide for clinical treatment decisions, and a target for glioblastoma therapy.
Keywords: temozolomide